Juridical Review of Land Tenure Dispute Between PTPN.VIII GoalPara Plantation and the Community of Margaluyu Village Sukaraja Sukabumi District - Fasya, Agus Imanudin; Fikri, Ahmad Ma'mun (Journal of Law, Politic and Humanities, 2025)
A conflict involving two or more parties claiming ownership rights to a property is known as a land ownership dispute. Land ownership conflicts, both vertical and horizontal, especially involving Dutch plantation properties, remain unresolved. The purpose of this study is to find out the process of land ownership by the community over the Business Use Rights (HGU) owned by the Goalpara Farm of PT Perkebunan Nusantara VIII, as well as the reasons behind land ownership and efforts to resolve conflicts that may arise. This research was conducted at Taman Goalpara PT Perkebunan Nusantara VIII in Sukaraja, Sukabumi Regency. The normative juridical approach is the methodology used, in which experience produces truth and offers a framework of proof to guarantee the validity of facts. The information used in this study includes, The method used is the Quantitative method, which is to collect data in an organized manner in accordance with the research conducted. Seen from the perspective of the Court Decision. PT. Perkebunan Nusantara VIII has filed a lawsuit with the Jakarta State Administrative Court. Judging from the National Land Law